SEIZURES – DIAGNOSIS AND TREATMENT AFTER CARDIAC SURGERY IN THE PEDIATRIC POPULATION - H. Mandzukovska (Македонско лекарско друштво = Macedonian medical association, 2018)
Introduction. Seizures are complications that can occur after cardiac surgery of congenital heart disease. Seizures are a symptom of disorders that happened in the brain and can be registerted with neurophysiology diagnostic procedures. A long-term neurodevelopmental follow up and electroencephalographic follow up is needed in purpose to minimize the occurrence of neurological disorders that can happen in the years later. Methods. If the seizures manifested the clinical status and vital parameters of the operated children in the postoperative period are followed-up (breathing, heart rate, blood pressure, neurological condition). Diagnostic examinations are carried out, EEG monitoring, head computed tomography. Anticonvulsant therapy is initiated. Results. From 57 operated patients, seizures appeared in four patients 3/57 (5.3%) in the first 24 hours. Seizures were classified as generalized tonic-clonic in one child (1.8%) and simple/complex partial also in 2 children (3.5%). The main risk factors for development are intracranial bleeding during cardiac surgery, prolonged duration of CPB of 81.5 min (range 11-196 minutes), and 29.2 min ( range 15 - 65 min) of x-clamp of aorta. Hypothermia implemented during the cardiac surgery was 32 C. Due to the prolonged cardiac surgery and deterioration of general condition, the following of postoperative period was also prolonged. Conclusions. The seizures are a rare complication that occurs in the early postoperative period. They are the first marker of brain dysfunction which requires a long-term monitoring of the condition. Seizures increase the risk factors for occurrence of dysfunctional and cognitive disturbances.
Keywords: neurological disorders; seizures; hypothermia